Impact of intra‐operative doppler ultrasound assistance during microsurgical varicocelectomy on operative outcome and sperm parameters. (7th May 2020) - Özkaptan, Orkunt; Balaban, Muhsin; Sevinc, Cüneyd; Çubuk, Alkan; Sahan, Ahmet; Akca, Oktay
Abstract: The microsurgical varicocelectomy is the gold standard treatment with a low recurrence rate and less postoperative complications. We compared the surgical outcomes and difficulty in intra‐operative vascular Doppler ultrasound‐assisted microscopic varicocelectomy (IVDU‐MV) with MV in primary and recurrent varicocele. A total of 228 infertile patients with clinically palpable varicocele were included in the study. One hundred fifteen patients were operated on with the standard MV approach, whereas the other 113 patients were operated on with IVDU‐MV. Perioperative outcomes, sperm parameters and operative difficulty of the procedure were evaluated. The operative times were significantly shorter for the IVDU‐MV group for primary and recurrent varicocele ( p = .001). Mean number of veins ligated for primary and recurrent varicocele was significantly higher in the IVDU‐MV group than in the MV group (6 ± 1.4 vs. 4.8 ± 1.8 and 3.7 ± 0.9 vs. 2.9 ± 1.2; p < .01). The increase in mean sperm motility was significantly higher in the IVDU‐MV group for both primary and recurrent varicocelectomy patients ( p < .05). A significant number of IVDU‐MV procedures were described as easy in both primary and recurrent varicocelectomy procedures ( p = .006). The use of Doppler ultrasound(US) revealed advantages in ligating veins, preserving arteries and improving sperm motility and facilitates the operation for the surgeon, especially during recurrent varicocele repair.